Primary Graft Dysfunction: The Role of Aging in Lung Ischemia-Reperfusion Injury - Roesel, Maximilian J.; Sharma, Nirmal S.; Schroeter, Andreas; Matsunaga, Tomohisa; Xiao, Yao; Zhou, Hao; Tullius, Stefan G. (Frontiers in Immunology, 2022)
Transplant centers around the world have been using extended criteria donors to remedy the ongoing demand for lung transplantation. With a rapidly aging population, older donors are increasingly considered. Donor age, at the same time has been linked to higher rates of lung ischemia reperfusion injury (IRI). This process of acute, sterile inflammation occurring upon reperfusion is a key driver of primary graft dysfunction (PGD) leading to inferior short- and long-term survival. Understanding and improving the condition of older lungs is thus critical to optimize outcomes. Notably, ex vivo lung perfusion (EVLP) seems to have the potential of reconditioning ischemic lungs through ex-vivo perfusing and ventilation. Here, we aim to delineate mechanisms driving lung IRI and review both experimental and clinical data on the effects of aging in augmenting the consequences of IRI and PGD in lung transplantation.